Alcohol policy process in Thailand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Auckland, New Zealand - Thaksaphon, Thamarangsi (Massey University, 2008)
The thesis describes and analyses the Thai alcohol policy process in the period 1997 - 2006, in order to investigate the characteristics and areas for potential improvement of the Thai alcohol policy process. The analysis used several extant public policy models. The models covered three aspects of the process at the macro leve l : stages of development, the characteristics and behaviours of maj or policy players, and the policy context. At the micro level the analysis employs concepts of agenda setting, policy formulation, policy implementation, monitoring and evaluation, stakeholder relationships and policy context. Information on Thai alcohol policy was collected from two sources: secondary data included official documents, literature, technical publications and mass media; pnmary data was collected through stakeholder interviews. Thai alcohol policy, during this period became more comprehensive and more oriented to public health. Problem-reduction values gained momentum while economic values remained significant. Thai policy stakeholders focused on the formulation process, while implementation, monitoring and evaluation were neglected. Limited resources, human capacity and ineffective management exacerbated this situation. Incrementalism characterised Thai alcohol policy formulation; existing policy or the policy precursor was very important to the decisions made. Limitations in the availability, accuracy and utilisation of knowledge about alcohol consumption, related problems and alcohol policy also affected the process. The Thai alcohol policy process became a more open public policy sphere for stakeholders. Many new players made major contributions to the process. The mechanisms stakeholders use to influence policy have become more complex and included: technical knowledge, the use of mass media and civil movements, and coordination among stakeholders. A centralised bureaucratic administration and personal and institutional interests are critical features for official stakeholders, while connection to high ranking officials and representation in the process are significant for interest groups. The Thai cultural context had a crucial impact on the alcohol policy process; cultural features which are not explicitly covered in the Western policy models utilised include cronyism, relationships, representation, commitment, negligence, and compromise. These characteristics make the Thai alcohol policy process difficult to fully explain in terms of the available public policy theories.
Keywords: Public policy; Policy and culture; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy